Application of 1-Dimensional and 2-Dimensional Solid-State Nuclear Magnetic Resonance Spectroscopy to the Characterization of Morphine, Morphine Hydrochloride, and Their Hydrates - Romañuk, Carolina Beatriz (2017)
The detailed knowledge of the solid forms of a drug is a key element in pharmaceutical development. Morphine (MOR) is an opiate alkaloid widely used to treat severe acute and chronic pain. Much of the available information on its solid state dates from several decades ago. In order to obtain updated and reliable information, 1-dimensional (1D) and 2-dimensional solid-state nuclear magnetic resonance spectroscopy were used and complemented with powder X-ray diffraction, FTIR, and Raman spectroscopy and thermal analysis. 13C cross-polarization with magic angle spinning 1D spectra accomplish a complete identification of the related forms of MOR. Remarkably, 1H-13C heteronuclear correlation spectra together with FTIR results gave clear evidence that neither MOR nor its hydrate crystallizes as a zwitterion. Our results indicate that the hydrogen bonds in the anhydrate forms have a different nature or strength than in their respective hydrates. The unique information obtained would be useful for the characterization of MOR as a bulk drug, dosage forms, and future developments.